Iddhipada 4: Principles Leading School Administration to Success - Haseesuk, Saifa (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2026)
This article aims to represent guidelines for implementing the Four Iddhipada to school administration for success followed by the Buddhist the principle showing of management that promote the work efficiency. The Four Iddhipada is the main principle leading to success in various business operations, including educational administrations, consisting of: 1) Chantha (love, satisfaction with what one has or what one has done), 2) Viriya (diligence in achieving one's goals), 3) Citta (attentiveness and readiness to take responsibility for the results that will be occurred), and 4) Vimansa is the diligence in inspecting for reasons in order to solve them using wisdom. Schools play an important role in the development of the country's youth. Therefore, it is essential to be the integration in management using the Buddhist principle to promote the balance to mobilize to the expected success.